Passion and perseverance: How the components of grit affect the probability of starting a business - Barrientos Oradini, Nicolás Pablo; Rubio, Andrés; Araya-Castillo, Luis; Boada-Cuerva, Maria; Vallejo-Velez, Mauricio (Frontiers in Psychology, 2022)
There is vast evidence that accounts for the association between entrepreneurial orientation (EO) and the probability of starting a business (PSB). However, there are not many studies that test how psychological factors moderate this relationship. A variable that has been little studied in this relationship is Grit. Grit is considered a personality trait defined as perseverance and passion for long-term goals. Grit considers two sub-dimensions, one linked to the consistency of interests (Grit-Passion) and the other linked to perseverance in the effort (Grit-Perseverance). The objective of this paper is to analyze the moderating role that both sub-dimensions of grit plays in the relationship between EO and PSB, considering its interaction with sociodemographic variables such as age, gender, and culture. This cross-sectional study has a sample of 1,761 participants, active workers (49.8% men; mean age 41.15 years, SD = 12.72 years; 22.9% Colombian and 77.1% Spanish). The EO scale and a Grit Scale were applied. In addition, participants were asked, based on their perception, how likely they were to start their own business within the next five years. A simple moderation analysis was considered to test the moderating role of grit in the relationship between EO and PSB. Subsequently, a double moderation analysis was carried out in order to identify which sociodemographic variables moderate the moderating effect of grit on the relationship in question. The results show that only the Grit-Passion component of grit moderates the relationship between EO and PSB. Regarding the sociodemographic variables, neither age, culture, nor gender showed a moderating effect on the moderation exercised by Grit-Passion in the relationship between OE and PSB. The results are discussed in terms of psychological capital, particularly with an emphasis on explaining why only the Grit-Passion shows a moderating effect on the relationship between EO and PSB, in detriment of Grit-Perseverance. In addition, the power of grit in the field of entrepreneurship is discussed, considering that its moderating effect is transversal to variations in age, gender and culture, as well as its relevance when considering interventions and pedagogical models in the field of entrepreneurship.